The global phenomenon of desertification in geography textbooks in Brazil - Albuquerque, Francisco Nataniel Batista de; da Silva, Vinícius Alves; Silva, Leonardo de Souza (Revista Ensino de Geografia (Recife), 2021)
Desertification is a problem in the dry regions of the globe, requiring prevention and combat actions, which necessarily involve school education. Given the above, the research analyzes the approach to the phenomenon of desertification in the 14 textbooks of Geography for High School approved by the National Textbook Program (2018), based on the evaluation of criteria as a conceptual definition, causes, effects, time and space scales and public policies and/or desertification mitigation measures. Among the results, we can highlight that 71% of the textbooks present at least one of the aspects analyzed with emphasis on five books (36%) with a satisfactory approach: ALMEIDA and RIGOLIN (2017), SOUZA et al. (2016), MOREIRA (2016), MARTINS et al. (2016) and LUCCI et al. (2016). Meanwhile, 29% of textbooks do not address the issue, making it difficult to adopt in schools in the Brazilian Semiarid Region and, consequently, fighting in the affected areas and making the scientific and political debate nationally invisible. As for the aspects of the phenomenon, the textbooks mainly address the causes, effects and spatialities of occurrence, precisely the dimensions of the phenomenon's empirical field to the detriment of the conceptual aspects and the political dimension to combat desertification.